A DNA repair disorder caused by de novo monoallelic DDB1 variants is associated with a neurodevelopmental syndrome. - White, Susan M; Bhoj, Elizabeth; Nellaker, Christoffer; Lachmeijer, Augusta M A; Marshall, Aren E; Boycott, Kym M; Li, Dong; Smith, Wendy; Hartley, Taila; McBride, Arran; Ernst, Michelle E; May, Alison S; et al. (Am J Hum Genet, 2021)
The DNA damage-binding protein 1 (DDB1) is part of the CUL4-DDB1 ubiquitin E3 ligase complex (CRL4), which is essential for DNA repair, chromatin remodeling, DNA replication, and signal transduction. Loss-of-function variants in genes encoding the complex components CUL4 and PHIP have been reported to cause syndromic intellectual disability with hypotonia and obesity, but no phenotype has been reported in association with DDB1 variants. Here, we report eight unrelated individuals, identified through Matchmaker Exchange, with de novo monoallelic variants in DDB1, including one recurrent variant in four individuals. The affected individuals have a consistent phenotype of hypotonia, mild to moderate intellectual disability, and similar facies, including horizontal or slightly bowed eyebrows, deep-set eyes, full cheeks, a short nose, and large, fleshy and forward-facing earlobes, demonstrated in the composite face generated from the cohort. Digital anomalies, including brachydactyly and syndactyly, were common. Three older individuals have obesity. We show that cells derived from affected individuals have altered DDB1 function resulting in abnormal DNA damage signatures and histone methylation following UV-induced DNA damage. Overall, our study adds to the growing family of neurodevelopmental phenotypes mediated by disruption of the CRL4 ubiquitin ligase pathway and begins to delineate the phenotypic and molecular effects of DDB1 misregulation.
Keywords: Adolescent; Alleles; Child; Child, Preschool; DNA Repair; DNA-Binding Proteins; Female; Humans; Male; Mutation; Neurodevelopmental Disorders; Phenotype; Syndrome

Pathogenic Variants in CEP85L Cause Sporadic and Familial Posterior Predominant Lissencephaly. - Tsai, Meng-Han; Muir, Alison M; Wang, Won-Jing; Kang, Yi-Ning; Yang, Kun-Chuan; Chao, Nian-Hsin; Wu, Mei-Feng; Chang, Ying-Chao; Porter, Brenda E; Jansen, Laura A; Sebire, Guillaume; Deconinck, Nicolas; et al. (Neuron, 2020)
Lissencephaly (LIS), denoting a "smooth brain," is characterized by the absence of normal cerebral convolutions with abnormalities of cortical thickness. Pathogenic variants in over 20 genes are associated with LIS. The majority of posterior predominant LIS is caused by pathogenic variants in LIS1 (also known as PAFAH1B1), although a significant fraction remains without a known genetic etiology. We now implicate CEP85L as an important cause of posterior predominant LIS, identifying 13 individuals with rare, heterozygous CEP85L variants, including 2 families with autosomal dominant inheritance. We show that CEP85L is a centrosome protein localizing to the pericentriolar material, and knockdown of Cep85l causes a neuronal migration defect in mice. LIS1 also localizes to the centrosome, suggesting that this organelle is key to the mechanism of posterior predominant LIS.
Keywords: Adolescent; Adult; Age of Onset; Animals; Centrosome; Child; Child, Preschool; Chromosome Aberrations; Classical Lissencephalies and Subcortical Band Heterotopias; Cytoskeletal Proteins; Female; Gene Knockdown Techniques; Genetic Variation; Heterozygote; Humans; Infant; Magnetic Resonance Imaging; Male; Mice; Mutation; Oncogene Proteins, Fusion; Pedigree; Seizures; Young Adult

Bioinformatics-Based Identification of Expanded Repeats: A Non-reference Intronic Pentamer Expansion in RFC1 Causes CANVAS. - Rafehi, Haloom; Szmulewicz, David J; Bennett, Mark F; Sobreira, Nara L M; Pope, Kate; Smith, Katherine R; Gillies, Greta; Diakumis, Peter; Dolzhenko, Egor; Eberle, Michael A; Barcina, María García; Breen, David P; et al. (Am J Hum Genet, 2019)
Genomic technologies such as next-generation sequencing (NGS) are revolutionizing molecular diagnostics and clinical medicine. However, these approaches have proven inefficient at identifying pathogenic repeat expansions. Here, we apply a collection of bioinformatics tools that can be utilized to identify either known or novel expanded repeat sequences in NGS data. We performed genetic studies of a cohort of 35 individuals from 22 families with a clinical diagnosis of cerebellar ataxia with neuropathy and bilateral vestibular areflexia syndrome (CANVAS). Analysis of whole-genome sequence (WGS) data with five independent algorithms identified a recessively inherited intronic repeat expansion [(AAGGG)] in the gene encoding Replication Factor C1 (RFC1). This motif, not reported in the reference sequence, localized to an Alu element and replaced the reference (AAAAG) short tandem repeat. Genetic analyses confirmed the pathogenic expansion in 18 of 22 CANVAS-affected families and identified a core ancestral haplotype, estimated to have arisen in Europe more than twenty-five thousand years ago. WGS of the four RFC1-negative CANVAS-affected families identified plausible variants in three, with genomic re-diagnosis of SCA3, spastic ataxia of the Charlevoix-Saguenay type, and SCA45. This study identified the genetic basis of CANVAS and demonstrated that these improved bioinformatics tools increase the diagnostic utility of WGS to determine the genetic basis of a heterogeneous group of clinically overlapping neurogenetic disorders.

Cerebral hypomyelination associated with biallelic variants of FIG4. - Lenk, Guy M; Berry, Ian R; Stutterd, Chloe A; Blyth, Moira; Green, Lydia; Vadlamani, Gayatri; Warren, Daniel; Craven, Ian; Fanjul-Fernandez, Miriam; Rodriguez-Casero, Victoria; Lockhart, Paul J; Vanderver, Adeline; et al. (Hum Mutat, 2019)
The lipid phosphatase gene FIG4 is responsible for Yunis-Varón syndrome and Charcot-Marie-Tooth disease Type 4J, a peripheral neuropathy. We now describe four families with FIG4 variants and prominent abnormalities of central nervous system (CNS) white matter (leukoencephalopathy), with onset in early childhood, ranging from severe hypomyelination to mild undermyelination, in addition to peripheral neuropathy. Affected individuals inherited biallelic FIG4 variants from heterozygous parents. Cultured fibroblasts exhibit enlarged vacuoles characteristic of FIG4 dysfunction. Two unrelated families segregate the same G > A variant in the +1 position of intron 21 in the homozygous state in one family and compound heterozygous in the other. This mutation in the splice donor site of exon 21 results in read-through from exon 20 into intron 20 and truncation of the final 115 C-terminal amino acids of FIG4, with retention of partial function. The observed CNS white matter disorder in these families is consistent with the myelination defects in the FIG4 null mouse and the known role of FIG4 in oligodendrocyte maturation. The families described here the expanded clinical spectrum of FIG4 deficiency to include leukoencephalopathy.

Pathogenic Variants in GPC4 Cause Keipert Syndrome. - Amor, David J; Stephenson, Sarah E M; Mustapha, Mirna; Mensah, Martin A; Ockeloen, Charlotte W; Lee, Wei Shern; Tankard, Rick M; Phelan, Dean G; Shinawi, Marwan; de Brouwer, Arjan P M; Pfundt, Rolph; Dowling, Cari; et al. (Am J Hum Genet, 2019)
Glypicans are a family of cell-surface heparan sulfate proteoglycans that regulate growth-factor signaling during development and are thought to play a role in the regulation of morphogenesis. Whole-exome sequencing of the Australian family that defined Keipert syndrome (nasodigitoacoustic syndrome) identified a hemizygous truncating variant in the gene encoding glypican 4 (GPC4). This variant, located in the final exon of GPC4, results in premature termination of the protein 51 amino acid residues prior to the stop codon, and in concomitant loss of functionally important N-linked glycosylation (Asn514) and glycosylphosphatidylinositol (GPI) anchor (Ser529) sites. We subsequently identified seven affected males from five additional kindreds with novel and predicted pathogenic variants in GPC4. Segregation analysis and X-inactivation studies in carrier females provided supportive evidence that the GPC4 variants caused the condition. Furthermore, functional studies of recombinant protein suggested that the truncated proteins p.Gln506 and p.Glu496 were less stable than the wild type. Clinical features of Keipert syndrome included a prominent forehead, a flat midface, hypertelorism, a broad nose, downturned corners of mouth, and digital abnormalities, whereas cognitive impairment and deafness were variable features. Studies of Gpc4 knockout mice showed evidence of the two primary features of Keipert syndrome: craniofacial abnormalities and digital abnormalities. Phylogenetic analysis demonstrated that GPC4 is most closely related to GPC6, which is associated with a bone dysplasia that has a phenotypic overlap with Keipert syndrome. Overall, we have shown that pathogenic variants in GPC4 cause a loss of function that results in Keipert syndrome, making GPC4 the third human glypican to be linked to a genetic syndrome.

Expanding the phenotypic spectrum of ARID1B-mediated disorders and identification of altered cell-cycle dynamics due to ARID1B haploinsufficiency. - Sim, Joe C H; White, Susan M; Fitzpatrick, Elizabeth; Wilson, Gabrielle R; Gillies, Greta; Pope, Kate; Mountford, Hayley S; Torring, Pernille M; McKee, Shane; Vulto-van Silfhout, Anneke T; Jhangiani, Shalini N; Muzny, Donna M; et al. (Orphanet J Rare Dis, 2014)
BACKGROUND: Mutations in genes encoding components of the Brahma-associated factor (BAF) chromatin remodeling complex have recently been shown to contribute to multiple syndromes characterised by developmental delay and intellectual disability. ARID1B mutations have been identified as the predominant cause of Coffin-Siris syndrome and have also been shown to be a frequent cause of nonsyndromic intellectual disability. Here, we investigate the molecular basis of a patient with an overlapping but distinctive phenotype of intellectual disability, plantar fat pads and facial dysmorphism. METHODS/RESULTS: High density microarray analysis of the patient demonstrated a heterozygous deletion at 6q25.3, which resulted in the loss of four genes including AT Rich Interactive Domain 1B (ARID1B). Subsequent quantitative real-time PCR analysis revealed ARID1B haploinsufficiency in the patient. Analysis of both patient-derived and ARID1B knockdown fibroblasts after serum starvation demonstrated delayed cell cycle re-entry associated with reduced cell number in the S1 phase. Based on the patient's distinctive phenotype, we ascertained four additional patients and identified heterozygous de novo ARID1B frameshift or nonsense mutations in all of them. CONCLUSIONS: This study broadens the spectrum of ARID1B associated phenotypes by describing a distinctive phenotype including plantar fat pads but lacking the hypertrichosis or fifth nail hypoplasia associated with Coffin-Siris syndrome. We present the first direct evidence in patient-derived cells that alterations in cell cycle contribute to the underlying pathogenesis of syndromes associated with ARID1B haploinsufficiency.
Keywords: Abnormalities, Multiple; Cell Cycle; Chromatin Assembly and Disassembly; DNA-Binding Proteins; Face; Female; Hand Deformities, Congenital; Haploinsufficiency; Humans; Intellectual Disability; Male; Micrognathism; Neck; Transcription Factors